The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/modpathol.2012.189
|View full text |Cite
|
Sign up to set email alerts
|

Testicular hilum and vascular invasion predict advanced clinical stage in nonseminomatous germ cell tumors

Abstract: Clinical staging is a critical step in the management of testicular germ cell tumors. Up to one-third of nonseminomatous germ cell tumors of the testis present with metastatic disease (clinical stages II and III). We investigated the predictors of metastatic disease at presentation in a cohort of 148 consecutive nonseminomatous germ cell tumors of the testis, over a 10-year period. The following clinical and pathologic features were evaluated: age, tumor size, dominant tumor histology, coagulative necrosis, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 25 publications
4
36
2
1
Order By: Relevance
“…This was not true of the smaller cut‐off values of 2 and 3 cm, respectively. These findings differ from those described previously in non‐seminomatous germ cell tumours in the lack of support for hilar soft tissue, epididymal invasion, and rete testis invasion as prognostic risk factors, as well as the recently revised AJCC staging of germ cell tumours, which includes hilar soft tissue and epididymal invasion and a cut‐off size of 3 cm …”
Section: Discussioncontrasting
confidence: 99%
“…This was not true of the smaller cut‐off values of 2 and 3 cm, respectively. These findings differ from those described previously in non‐seminomatous germ cell tumours in the lack of support for hilar soft tissue, epididymal invasion, and rete testis invasion as prognostic risk factors, as well as the recently revised AJCC staging of germ cell tumours, which includes hilar soft tissue and epididymal invasion and a cut‐off size of 3 cm …”
Section: Discussioncontrasting
confidence: 99%
“…In the 15 patients, vascular invasion was found in 13 (86.6%) patient. Yilmaz et al [3] found that hilar soft tissues invasion is also strongly associated with metastatic disease in NS germ cell tumors [3]. In our study, 11 of 15 patients were NS germ cell tumors.…”
Section: Discussionmentioning
confidence: 60%
“…In our study, 11 of 15 patients were NS germ cell tumors. Although the majority of patients were NS germ cell tumors as in Yilmazs et al [3] There is no association between distant organ metastasis and hilar soft tissue involvement.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Currently, this tumor should be staged as pT1 or pT2 (depending on the absence or presence of lymphovascular invasion). However, it clearly represents extratesticular extension of the tumor and likely a higher risk of recurrence [281,282]. Other criticisms to the system include the disproportionate weight conferred to the invasion of the tunica vaginalis and the scrotum, which are relatively rare phenomena [282], and the lack of differentiation of the pattern of involvement of the spermatic cord, which may be involved by direct extension (Fig.…”
Section: M0mentioning
confidence: 96%